BOSCIA ALBITRUNCA: REVIEW OF ITS BOTANY, MEDICINAL USES, PHYTOCHEMISTRY, AND BIOLOGICAL ACTIVITIES: ETHNOPHARMACOLOGY OF BOSCIA ALBITRUNCA - ALFRED MAROYI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Boscia albitrunca is a medium-sized tree widely used as herbal medicine in Southern Africa. The current study critically reviewed the botany, medicinal uses, phytochemistry, and pharmacological activities of B. albitrunca. Literature on botany, medicinal uses, phytochemical, and biological activities of B. albitrunca was collected from multiple internet sources including Elsevier, Google Scholar, SciFinder, Web of Science, PubMed, BMC, Science Direct, and Scopus. Complementary information was gathered from pre-electronic sources such as books, book chapters, theses, scientific reports, and journal articles obtained from the university library. This study revealed that the species is used as herbal medicine in 75.0% of the countries in Southern Africa where the species is indigenous. The bark, leaves, and roots of B. albitrunca are mainly used as herbal medicines for constipation, epilepsy, hemorrhoids, headache, human immunodeficiency virus/acquired immune deficiency syndrome, skin diseases, syphilis, and as ethnoveterinary medicine. Ethnopharmacological research identified phenolic compounds, alkaloids, coumarins, flavonoids, saponins, steroids, tannins, and triterpernoids from leaves of B. albitrunca. The crude extracts of the species and the compound martynoside isolated from B. albitrunca exhibited antibacterial and antifungal activities. B. albitrunca should be subjected to detailed phytochemical, pharmacological, and toxicological evaluations aimed at correlating its medicinal uses with its phytochemistry and pharmacological activities.